The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2023
DOI: 10.1096/fj.202201962r
|View full text |Cite
|
Sign up to set email alerts
|

TFAP2C inhibits cell autophagy to alleviate myocardial ischemia/reperfusion injury by regulating miR‐23a‐5p/SFRP5/Wnt5a axis

Abstract: Myocardial ischemia/reperfusion (MI/R) injury contributes to severe injury for cardiomyocytes. In this study, we aimed to explore the underlying mechanism of TFAP2C on cell autophagy in MI/R injury. MTT assay measured cell viability.The cells injury was evaluated by commercial kits. IF detected the level of LC3B.Dual luciferase reporter gene assay, ChIP or RIP assay were performed to verify the interactions between crucial molecules. We found that TFAP2C and SFRP5 expression were decreased while miR-23a-5p and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 48 publications
0
1
0
Order By: Relevance
“…IKZF3 [69], hsa-mir-146a-5p [607], BRCA1 [608] and NFKB1 [609] can participate in the occurrence and development of MS. IKZF3 [239], TAB2 [256], CCR4 [231], LTF (lactotransferrin) [249], CDH1 [266], BRCA1 [610], NFKB1 [611] and FOXO3 [612] might play an important role in the occurrence and development of autoimmune disease. TAB2 [131], CCR4 [112], LTF (lactotransferrin) [126], hsa-mir-146a-5p [613], hsa-mir-8485 [614], BRCA1 [615], NFKB1 [616], TEAD1 [617], TFAP2C [618], FOXO3 [619 and NRF1 [620] risk factors have been shown to increase susceptibility to cardiovascular diseases. Several studies have shown that TAB2 [131], LTF (lactotransferrin) [487], BRCA1 [621], NFKB1 [622], TEAD1 [623], FOXO3 [624] and NRF1 [625] can be involved in the disease progression of obesity ., Altered expression of CCR4 [280], LTF (lactotransferrin) [295], CDH1 [313], CFTR (CF transmembrane conductance regulator) [317], hsa-mir-146a-5p [626], hsa-mir-195-5p [627], hsa-mir-4739 [628], HNF4A [629], NFKB1 [630], NR2F1 [631], FOXO3 [632] and NRF1 [633] are observed in diabetes mellitus.…”
Section: Discussionmentioning
confidence: 99%
“…IKZF3 [69], hsa-mir-146a-5p [607], BRCA1 [608] and NFKB1 [609] can participate in the occurrence and development of MS. IKZF3 [239], TAB2 [256], CCR4 [231], LTF (lactotransferrin) [249], CDH1 [266], BRCA1 [610], NFKB1 [611] and FOXO3 [612] might play an important role in the occurrence and development of autoimmune disease. TAB2 [131], CCR4 [112], LTF (lactotransferrin) [126], hsa-mir-146a-5p [613], hsa-mir-8485 [614], BRCA1 [615], NFKB1 [616], TEAD1 [617], TFAP2C [618], FOXO3 [619 and NRF1 [620] risk factors have been shown to increase susceptibility to cardiovascular diseases. Several studies have shown that TAB2 [131], LTF (lactotransferrin) [487], BRCA1 [621], NFKB1 [622], TEAD1 [623], FOXO3 [624] and NRF1 [625] can be involved in the disease progression of obesity ., Altered expression of CCR4 [280], LTF (lactotransferrin) [295], CDH1 [313], CFTR (CF transmembrane conductance regulator) [317], hsa-mir-146a-5p [626], hsa-mir-195-5p [627], hsa-mir-4739 [628], HNF4A [629], NFKB1 [630], NR2F1 [631], FOXO3 [632] and NRF1 [633] are observed in diabetes mellitus.…”
Section: Discussionmentioning
confidence: 99%
“…In this issue of the Korean Circulation Journal , Zeng et al 1) demonstrated that long non-coding RNA (lncRNA) prostate androgen regulated transcript 1 (PART1) was responsible for inducing cardiomyocyte autophagy in the myocardial ischemia-reperfusion injury model. LncRNA PART1 was downregulated by ischemic stress in cardiomyocytes, resulting in significant autophagy and apoptosis.…”
mentioning
confidence: 99%